Cymbopogon citratus and cymbopogon nardus essential oil components - FTIR, Chemometrics assessment and identification using GC-MS - Hazrulrizawati, Abd Hamid (The Malaysian Analytical Sciences Society, 2023)
Cymbopogon citratus and Cymbopogon nardus essential oil are high-value natural products due to their special qualities and commercial significance. In this work, the volatile compounds of the C. citratus and C. nardus natural essential oils obtained by hydro distillation and commercial sources using gas chromatography-mass spectrometry (GC-MS), Fourier transformation infrared spectroscopy (FTIR) and chemometrics methods were systematically detected and identified. The GC-MS results indicated that the main compound in the natural essential oil of C. citratus is citral while citronellal commercial samples of both Cymbopogan species are positively significant. Based on the results of GC-MS, citral was the major component in C. citratus while citronellal was the major component in C. nardus. Analyzing the FTIR data using principal component analysis (PCA), hierarchical cluster analysis (HCA), and discriminant analysis (DA) further revealed that the chemical composition of natural essential oils C. citratus and C. nardus samples were significantly different from commercial samples. This study revealed the first insight into metabolite compositional differences among C. citratus and C. nardus using quick and affordable analytical procedures.